Transforming School Libraries into Educational Literacy-Based Learning Centers in Elementary Schools - Muh. Khaerul Ummah BK; Hamna; Taspia; Sabrina (Program Studi PGSD Universitas Madako Tolitoli, 2025)
The transformation of school libraries into literacy-based learning centers in elementary schools is a strategy to improve students' reading and critical thinking culture. The purpose of this study is to analyze the managerial role of school library managers in building a reading literacy culture at SDN Sandana. Data collection techniques by conducting observation activities, interviews with one of the educators to collect information or data to support data analysis. The results of the study show that effective managerial supervision plays an important role in supporting the transformation by proving that respondents' satisfaction with the following aspects: (1) Innovation of School Library Facilities (87.46%), (2) Development of Library Collections (83.56%), (3) Evaluation of Library Standard Operating Procedures (SOP) (84.39%), (4) Library Human Resource Management (84.20%), and (5) Development of Literacy Movement in the School Environment (83.12%). The implication of this research lies in strengthening the role of libraries as a dynamic learning environment in improving students' overall educational literacy.